2021
DOI: 10.3390/vaccines9040353
|View full text |Cite
|
Sign up to set email alerts
|

Immune Responses Elicited by Live Attenuated Influenza Vaccines as Correlates of Universal Protection against Influenza Viruses

Abstract: Influenza virus infection remains a major public health challenge, causing significant morbidity and mortality by annual epidemics and intermittent pandemics. Although current seasonal influenza vaccines provide efficient protection, antigenic changes of the viruses often significantly compromise the protection efficacy of vaccines, rendering most populations vulnerable to the viral infection. Considerable efforts have been made to develop a universal influenza vaccine (UIV) able to confer long-lasting and bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 129 publications
(148 reference statements)
1
12
0
Order By: Relevance
“…Importantly, there was no reduction in homologous HAI or serum IgG titers in ferrets immunized with recombinant LAIV+4M2e candidates, relative to the traditional LAIV virus, suggesting that none of the genetic modifications had an impact of influenza virus-specific humoral immunity. In line with previously published data, immunization with unmodified influenza virus (i.e., H3N2 LAIV) did not elicit notable levels of M2e-binding antibodies in ferrets [ 33 ]. However, the insertion of the 4M2e cassette into LAIV genome significantly increased the M2e-specific antibody levels, with the LAIV/HA+4M2e variant being remarkably more immunogenic than the LAIV/NS+4M2e counterpart.…”
Section: Discussionsupporting
confidence: 89%
“…Importantly, there was no reduction in homologous HAI or serum IgG titers in ferrets immunized with recombinant LAIV+4M2e candidates, relative to the traditional LAIV virus, suggesting that none of the genetic modifications had an impact of influenza virus-specific humoral immunity. In line with previously published data, immunization with unmodified influenza virus (i.e., H3N2 LAIV) did not elicit notable levels of M2e-binding antibodies in ferrets [ 33 ]. However, the insertion of the 4M2e cassette into LAIV genome significantly increased the M2e-specific antibody levels, with the LAIV/HA+4M2e variant being remarkably more immunogenic than the LAIV/NS+4M2e counterpart.…”
Section: Discussionsupporting
confidence: 89%
“…Excellent clinical protection, consistent with the absence of replication-competent virus in the lungs of challenged animals, and robust antibody responses shortly after challenge do, however, demonstrate the strong protective potential of this vaccine against different SARS-CoV-2 variants. In addition, vaccination with a live attenuated virus may offer better protection from (re)infection than vaccines that carry only a single antigen, because all SARS-CoV-2 proteins may trigger stronger cytotoxic T cell responses ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously theorised that sub-neutralising antibody levels and activation of FcγRI and FcγRIIA could promote viral cell entry, replication, and subsequent antigen presentation and immunogenicity of live attenuated viral vaccines [ 127 ]. However, a recent review has noted that in the context of influenza, LAIVs have been repeatedly shown to be safe and effective in animal models with no indications of VAERD or ADE [ 128 ]. A study by Winarski et al sought to evaluate the effect of monoclonal antibodies (mAbs) on influenza disease in a mouse model [ 129 ].…”
Section: Foreseeing Unexpected Outcomes Of Universal Vaccinationmentioning
confidence: 99%